AL-QUR’AN DAN PSIKOLOGI; MEMAHAMI KEPRIBADIAN MANUSIA PERSPEKTIF AL-QUR’AN - Yusron, M. Agus (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2022)
The human psychic dimension is the most important part that forms the human personality. The attitude shown in everyday life is a manifestation of what is contained in each individual. The Qur'an as the best guide of all time, both for Muslims and non-Muslims, certainly discusses all things related to humans, including matters or about human personality. In this study, using qualitative methods, then conducting research by reviewing related literature (liberary research), the researchers tried to explore the human personality from the perspective of the Qur'an, by examining related verses (about humans and their personalities), then juxtaposed with the theories of modern psychologists. In general, this study found that in the Qur'an there are elements of human personality; namely an-nafs, al-aql, and lust. The three of them will later shape the dynamics of the human personality at three levels; namely muthmainnah, lawwamah, and ammarah bi as-sû`. This is in line with the theory of Sigmund Freud, a Psychoanalyst, where in humans there are three personality drive systems; namely the id, ego, and superego. The id is more similar to ammarah, because they both prioritize individual aspects without thinking about any risks, the super ego is similar to muthmainnah, because it is formed from the environment or education. While the ego is similar to lawwamah, because it functions as a mediator or controller between the id and the super ego.